2018
DOI: 10.1017/dmp.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

The Gillette Stadium Experience: A Retrospective Review of Mass Gathering Events From 2010 to 2015

Abstract: At a single venue hosting a variety of events across a 6-year period, we demonstrated significant variations in presentation and transport rates. Weather, gender, event type, and age all play important roles. Our analysis, while representative only of our specific venue, may be useful in developing response plans and staffing models for similar mass gathering venues. (Disaster Med Public Health Preparedness. 2018;page 1 of 7).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In addition, other factors such as age, gender, type of event, and weather conditions have an important role in the patient presentation and required health care. 73 The results of our review indicate that the health conditions of participants in the MGs are related to the type of MG. On the other hand, it seems that the basic characteristics of participants in each type of MG are different. For example, the participants of the Hajj are older than those in other MGs, therefore, chronic diseases may be an additional threat for these participants and health care providers.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, other factors such as age, gender, type of event, and weather conditions have an important role in the patient presentation and required health care. 73 The results of our review indicate that the health conditions of participants in the MGs are related to the type of MG. On the other hand, it seems that the basic characteristics of participants in each type of MG are different. For example, the participants of the Hajj are older than those in other MGs, therefore, chronic diseases may be an additional threat for these participants and health care providers.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, temperature was identified as a potential contributor to spectator medicine in outdoor events. Goldberg et al reported that, for cold weather events, transport rates increased at colder temperatures [ 20 ]. Feldman et al reported that in Ontario’s Golden Horseshoe region during the 2015 Pan American and Parapan American Games 7827 more patients visited the physician’s office on days with a daily maximum temperature of 35 °C than of 25 °C [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerts, compared to sporting games, festivals, and entertainment events, generated the highest PPRs. 16 The availability of alcohol and other drugs is correlated to this finding, considering that almost twice as many patients presented for medical attention for intoxication at concerts compared with the other events. 16…”
Section: Event Typementioning
confidence: 98%
“…Environmental factors that influence patient presentations at mass gatherings, and are reported in the literature, include crowd attendance and density, venue characteristics (unbound versus bound; extended or focused; and local terrain), type of event, outdoor or indoor, weather (temperature and humidity), availability of alcohol or drugs, and whether attendees are predominantly seated or mobile. 5 There are many different ways of reporting environmental variables within the literature; these include wind speed, 6 dew point, [7][8][9][10] time of day and day of week, 7,11 air quality, [12][13][14] precipitation, 9,10,[14][15][16][17] Wet-Bulb Globe Temperature index (WBGT), 18 historical data, 7,8,11,12,17,[19][20][21][22] cold weather, 7,14,15,17,[23][24][25][26] allergic reactions, 27 availability of free water, 8,19,24,28 altitude, 15 and the presence of ethanol. 7,17,20,…”
Section: Introductionmentioning
confidence: 99%